A Modified Cover Parameter Value for the Universal Soil Loss Equation - Jemison, Roy L. (Arizona-Nevada Academy of Science, 1984)
From the Proceedings of the 1984 Meetings of the Arizona Section - American Water Resources Assn. and the Hydrology Section - Arizona-Nevada Academy of Science - April 7, 1984, Flagstaff, Arizona === The Universal Soil Loss Equation (USLE) was formulated for estimating soil loss from agricultural lands in the eastern United States. It has also proven to be useful in assisting land managers make better decisions for other land uses. Studies have shown that when the equation is used in areas other than where it was developed, predictions may be inadequate due to variations in estimates of the environmental parameters used in the equation. Ten years of rainfall, runoff, and sediment yield data collected by the USDA /Agricultural Research Service were used to evaluate several cover parameter values (C) presently in use in the Southwest. Preliminary analysis of data showed no statistical differences between calculated and measured cover parameter values.